Tasawuf Underground: Menumbuhkan Self-Awareness Anak Jalanan Dalam Kesadaran Melaksanakan Ibadah - Agustina Norma Pratama (Syntax Idea, 2022)
Children are the next generation who inherit the ideals of the nation's struggle which have an important role in the continuation of the existence of the nation and state in the future. Thisstudy aims to find out (1) The Worship Consciousness of Street Children in Subconscious Sufism. (2) Efforts of Subconscious Sufism in fostering the self-awareness of street children in carrying out worship. (3) Implications of the formation of self-awareness on the consciousness of street children in subconscious Sufism. This research is a qualitative research and field research using a case study approach. The subjects of this study were the founders of underground Sufism and street children of underground Sufism. The research location is under the Tebet Bridge, South Jakarta. Data collection techniques through observation, interviews and documentation. The results showed that the awareness of street children worshipping in underground Sufism was initially very low. It is shown by being undesirable to worship, consume illegal drugs, busk in the streets, and be homeless. The steps taken by underground Sufism to cultivate self-awareness in worship are to approach with reference to the theory of social concentration in five stages 1) Orientation stage 2) Affective exploration exchange 3) Affective exchange 4) Stable exchange 5) Depenetration. Then continued by introducing worship to street children with stages 1) understanding proselytizing 2) understanding haraki 3) understanding tandzhimi The implication of the efforts of underground Sufism in cultivating the self-awareness of street children is to carry out worship that there is a change in behavior in street children under his guidance which includes, wanting to worship, thinking, learning the Qur'an. a, and want to go to school.